Oral hygiene behaviors and caries experience in Northwest PRECEDENT patients. Issue 6 (27th April 2014) - Rothen, Marilynn; Cunha‐Cruz, Joana; Zhou, Lingmei; Mancl, Lloyd; Jones, Jackie S.; Berg, Joel; the Northwest PRECEDENT network
Abstract Objectives To investigate the association between oral hygiene behaviors (toothbrushing, water rinsing after brushing, interproximal cleaning, and adjunctive use of fluoride products) and recent caries (past 24 months) in a random sample of patients in Northwest PRECEDENT practices. Methods Practitioner‐members of Northwest PRECEDENT, a dental practice‐based research network, conducted a longitudinal study on caries risk assessment. At baseline, patients completed a questionnaire on oral self‐care, snacking, health, and socio‐demographics. A dental examination recorded readily visible heavy plaque and decayed, missing, and filled teeth; chart review captured new caries and treatments in the previous 24 months. Bivariate and multiple generalized estimating equations (GEE) log‐linear regression models stratified by age‐groups were used to relate oral hygiene behaviors to the primary outcome of mean dental caries in the past 24 months on data from 1400 patients in 63 practices. The primary exposure of interest was fluoride toothbrushing frequency. Results Fluoride toothbrushing once per day or twice or more per day by patients 9–17 was significantly associated with a 50% lower mean caries rate compared with fluoride toothbrushing less than once per day, after adjustment for covariates [rate ratios (RR) = 0.5; 95% confidence intervals (CI) = 0.3–0.8]. After adjustment, for patients 18–64, fluoride toothbrushing two or more times per day was significantly associated with a 40% lower recent mean caries rate (RR = 0.6; 95% CI = 0.4–0.9); in patients 65+, twice a day or more fluoride toothbrushing was not associated with lower caries rates (RR = 1.1; 95% CI = 0.7–1.8). Of the other oral hygiene variables, after adjustment, patients 18–64 who rinsed with water after brushing had a 40% lower mean caries rate compared with no rinsing (RR = 0.6; 95% CI = 0.4–0.9) and the presence of readily visible heavy plaque was significantly associated with an increase in the mean caries rate for patients 18–64 (RR = 1.6; 95% CI = 1.2–2.2) and 65+ (RR = 2.5; 95% CI = 1.8–3.5). Conclusions In the present study, the frequency of fluoride toothbrushing and the presence of readily visible heavy plaque were the factors most strongly associated with mean caries rate. In young patients with permanent dentition, the daily application of fluoride toothpaste appears more important than emphasis on thorough plaque removal. While for adults, the protective effect of twice daily fluoride toothbrushing disappears with advancing age and the presence of readily visible heavy plaque becomes increasingly associated with caries risk.